Intestinal flora alterations in patients with early chronic kidney disease: a case-control study among the Han population in southwestern China. Issue 6 (June 2020) - Hu, Qiongdan; Wu, Kaiyan; Pan, Wei; Zeng, Yan; Hu, Keqin; Chen, Dingguo; Huang, Xinchun; Zhang, Qiong
Objective: In this case–control study, we retrospectively analyzed the intestinal flora compositions of patients with early-stage chronic kidney disease (CKD). Methods: Forty-seven patients with early CKD who were treated at the Traditional Chinese Medicine Hospital between March and October 2018 were enrolled, and 150 healthy volunteers were enrolled in the healthy control group. Fresh stool samples were collected. The V3–V4 region of the bacterial 16S rRNA was amplified via PCR. Biterminal sequencing was performed using the Illumina MiSeq platform. The flora compositions were compared between the two groups. Results: The Chao1 and Shannon indices showed significantly lower intestinal flora diversity and abundances in the CKD group than in the healthy controls. Beta diversity analysis revealed notable differences in the intestinal flora compositions between the groups. At the phylum level, Actinobacteria and Proteobacteria abundances were significantly higher in the CKD group. Thirty-one species differed significantly between both groups, among which, differences in Ruminococcus and Roseburia displayed the highest diagnostic values for distinguishing CKD patients from healthy controls. Conclusions: Intestinal flora compositions are altered in early-stage CKD patients among the Han population in southwestern China.